2009
DOI: 10.1258/jmb.2009.009031
|View full text |Cite
|
Sign up to set email alerts
|

George Guthrie's clinical trial at the Napoleonic War Battle of Toulouse in 1814

Abstract: George James Guthrie (1785-1856) was a British military surgeon who came to prominence during the Napoleonic Wars (1803-15). He wrote several books on military surgery and was President of the Royal College of Surgeons of England three times. However, his most innovative and important achievement has largely gone unrecognised by modern historians. In 1814, at the battle of Toulouse in the Peninsular Campaign, he performed a landmark early trial of the treatment of musket wounds to the thigh. Here we not only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…71 In contrast, Guthrie conducted an early clinical trial of sorts that demonstrated the importance of prompt amputation for compound femur fractures resulting from GSW. 72 , 73…”
Section: Institutionalization Of Gsw Management In the Early Modern Eramentioning
confidence: 99%
“…71 In contrast, Guthrie conducted an early clinical trial of sorts that demonstrated the importance of prompt amputation for compound femur fractures resulting from GSW. 72 , 73…”
Section: Institutionalization Of Gsw Management In the Early Modern Eramentioning
confidence: 99%